Análisis de la multimedia como herramienta de comunicación en el arte visual ecuatoriano. - Melgarejo Sánchez, Danny Gabriel (2019)
This document for certification is relevant and timely for the creation of new works or artistic projects that include multimedia as a communication tool in Ecuadorian visual art. Objective technological functions converted or transformed into multimedia art as well as the advantages that promote and confirm it as a new and outstanding alternative in the experimental artistic environment in our country. The methodological design of this introspective research, qualitative perspective and interpretative paradigm, makes use of information gathering techniques such as the survey, the interview and the bibliographic review around two main themes, multimedia and art. Subsequently, the data collected were recorded in formats and coded for analysis and interpretation in order to resolve theoretical elements that argue the central theme of the investigation, what can be verified at the end of the document.